2021
DOI: 10.3892/mmr.2021.12551
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 attenuates high uric acid‑induced endoplasmic reticulum stress, inflammation and vascular endothelial cell dysfunction by activating Sirt1

Abstract: Uric acid (UA) is the final oxidation product of purine metabolism. Hyperuricemia has been previously reported to contribute to vascular endothelial dysfunction and the development of cardiovascular diseases, metabolic syndrome and chronic kidney diseases. In addition, it has been reported that fibroblast growth factor 21 (FGF21) can exert regulatory effects on UA-induced lipid accumulation. Therefore, the present study aimed to investigate the possible role of FGF21 in HUVEC cell injury induced by UA. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“… 41 , 42 Overexpression of FGF21 in endothelial cells can reduce oxidative stress and improve endothelial function. 43 As for the role of FGF21 in UA-induced VECI, Rong and coworkers demonstrated that FGF21 could attenuate high UA-induced endothelial. 43 Our results demonstrated that FGF21 knockdown abrogated the suppressive effect of TSA on inflammatory factor release and ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 , 42 Overexpression of FGF21 in endothelial cells can reduce oxidative stress and improve endothelial function. 43 As for the role of FGF21 in UA-induced VECI, Rong and coworkers demonstrated that FGF21 could attenuate high UA-induced endothelial. 43 Our results demonstrated that FGF21 knockdown abrogated the suppressive effect of TSA on inflammatory factor release and ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“… 43 As for the role of FGF21 in UA-induced VECI, Rong and coworkers demonstrated that FGF21 could attenuate high UA-induced endothelial. 43 Our results demonstrated that FGF21 knockdown abrogated the suppressive effect of TSA on inflammatory factor release and ROS generation. Moreover, FGF21 knockdown aggravated UA-induced endothelial dysfunction and endothelial–interstitial transformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a hyperuricemic concentration, 600 µM, leads cells to senescence [ 69 ] and inhibition of migration [ 70 ]. Higher concentrations (720 µM) induced ER stress [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…α‐Lipoic acid inhibited EC apoptosis and enhanced NO production in both in vitro and in vivo HUA models by attenuating oxidant stress and activating Akt signaling 113 . Fibroblast growth factor 21 (FGF21) attenuated ED induced by high levels of UA in HUVECs by activating Sirt1, which was manifested as the attenuation of oxidative stress, ER stress, and inflammation 70 . Collectively, although not an official recommendation, optimal pharmacological treatments might be an important approach to combat HUA‐induced ED.…”
Section: Intervention Strategiesmentioning
confidence: 99%